The dazzling book report - O'Connor, Jane; Preiss-Glasser, Robin; Enik, Ted (New York : HarperCollins Publishers, 2009)
Nancy is determined to make the cover of her very first book report as fancy as she can, but she spends so much time on it that she has no time to write about the book.
Keywords: Homework; Schools; Vocabulary; Schools; Vocabulary; Homework; High interest-low vocabulary books